Fourth Industrial Revolution and Evolution of Data Science: Challenges for Official Statistics - Osuolale Peter Popoola; Olawale Nureni Adeboye (ZBW – Leibniz Information Centre for Economics, 2023)
Fourth Industrial Revolution is describes as exponential growth of several key technological fields' concepts, such as intelligent materials, cloud computing, cyber-physical systems, data exchange, the Internet of things and blockchain technology. At its core, data represents a post-industrial opportunity. The effects of technologies have provided new avenues of data for official statistics, which can then be harnessed through the power of data science. However, as data continue to grow in size and complexity; new algorithms need to be developed so as to learn from diverse data sources. The limitation of conventional statistics in managing and analyzing big data has inspired data analysts to venture into data science. Data Science is a combination of multiple disciplines that use statistics, data analysis, and machine learning to analyze data, and extract knowledge and insights from it. These swathes of new digital data are valuable for official statistics. This paper links industrial eras to the evolution of statistics and data; it examines the emergence of big data and data science, what it means, it benefits and challenges for official statistics
Keywords: 330; Industrial Eras; Data Evolution; Big Data Revolution; Data Science; Official Statistics